Immediate and long-term results of bronchial artery embolisation for life-threatening hemoptysis in bronchiectasis - M., Rajani; S. M., Asharaf; V., Achuthan; D.K., Manoj (International Journal of Research in Medical Sciences, 2017)
Background: Bronchial artery embolization (BAE) has been established as an effective technique in the emergency treatment of life-threatening hemoptysis, but few data concerning long-term results of the procedure are available The aim of this study was to analyze the immediate and long-term results of bronchial artery embolization (BAE) for hemoptysis due to bronchiectasis. Methods: Twenty five patients (aged 28–76 years) who underwent bronchial artery embolization with polyvinyl alcohol particles, gelatin sponge and coil for massive or continuing moderate hemoptysis caused by bronchiectasis were included in the study. These patients were followed up for 3 years. Initially patients were followed up monthly for 6months by clinical examination. Then yearly follow up by clinical and radiological examination. Results analyzed using SPSS 16 version. Results: In our study16 patients (64%) were males. 11 patients (44%) had bilateral bronchiectasis.14 patients (56%) had no rebleeding in the three year follow-up period. Only 8% developed rebleeding within 24hrs.Only one patient (4%) developed massive hemoptysis within one month and died. Other rebleed were very minimal. In our study there was no significant relation with side of bronchiectasis and rebleed. Conclusions: Bronchial artery embolisation can yield immediate and long-term benefit in patients with hemoptysis due to bronchiectasis.